Generative AI for industry transformation: a systematic review of ChatGPT’s capabilities and integration challenges - Salih, Sayeed; Husain, Omayma; Abdalla, Elfadil Abdalla Mohamed; Ibrahim, Ashraf Osman; Hassan Abdalla Hashim, Aisha; Elshafie, Hashim; Motwakel, Abdelwahed (International Journal of Computer Science and Network Security, 2025)
The rapid advancement of Generative Artificial Intelligence (GAI), particularly OpenAI’s ChatGPT, has significantly transformed various industries by enhancing efficiency, reducing operational costs, and fostering innovation. This systematic review explores the applications and integration challenges of ChatGPT across six key sectors: tourism and travel, banking and finance, construction, software solutions, supply chain and transportation, and digital marketing and social media. The findings demonstrate ChatGPT's versatility, ranging from enhancing project management and automating customer support to assisting with code development, route optimization, and marketing strategy. Data protection, system integration, and worker adaption are some of the obstacles preventing its widespread implementation, despite its revolutionary potential. An overview of ChatGPT's alignment with Industry 5.0 objectives of sustainability and human-centric innovation is given in this paper, along with helpful suggestions for removing integration obstacles. By addressing the gaps in existing research, the review lays the groundwork for future investigations into the strategic dissemination of GAI technology across industries.